'Photonic jets' from dielectric microaxicons. (31st August 2015) - Geints, Yu E; Zemlyanov, A A; Panina, E K
Abstract We consider a specific spatially localised light structure, namely, a 'photonic jet' formed in the near field upon scattering of an optical wave in a dielectric micron particle. Dimensional parameters and intensity of a photonic jet from microaxicons of different spatial orientation are studied theoretically. It is found for the first time that an axicon-generated photonic jet has in this case a substantially larger length compared with the case of a jet formed on a spherical particle.